Trends in Place of Death in Brazil And Analysis of Associated Factors in Elderly Populations From 2002 to 2013 - Fernando Cesar Iwamoto Marcucci; Marcos Aparecido Sarria Cabrera; John Patrick Rosenberg; Patsy Yates (Brazilian Society of Geriatrics and Gerontology, 2024)
Background: Place of death (POD) distribution is influenced by sociocultural aspects, economic conditions and public policies. It is a central concern in end-of-life support and for healthcare system management, but there is limited information about POD in middle-income countries such as Brazil. Methods: Population data collected from the Brazilian Information about Mortality System were used to identify national and regional mortality rates, from 2002 to 2013. POD distribution was compared between age groups (<60 or ≥60 years old), and for gender and marital status in elderly population. Differences across national regions were analyzed. Results: In Brazil, POD is mostly allocated in hospitals with mean of 66.7%, followed by 21.4% at home. Other health care facilities account for less than 3% of all deaths. The number of deaths in older ages has increased. There were differences in POD distribution among regions. The North and the Northeast, for example, reported higher rates of home deaths compared with other regions. For the elderly population, there was a little difference between gender in POD distribution, and being married increased the odds of dying in hospital settings. Conclusion: Deaths in Brazil is limited to hospital and at home occurrences. In-hospital rates are increasing over the last years, while deaths at home have decreased despite the increase in number of deaths in older ages and due non-communicable diseases. POD distribution may be influenced by social and demographic factors, but specific health policies to support end-of-life care is limited in Brazil.